Preparation method of natural polysaccharide-based degradable high-strength antibacterial hydrogel

By preparing natural polysaccharide-based degradable high-strength antibacterial hydrogel, the problem of insufficient mechanical properties and antibacterial properties of cartilage defect repair materials is solved, and the complete degradation and low-cost efficient repair effect is achieved.

CN119258271APending Publication Date: 2025-01-07BEIJING HOSPITAL +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411296145.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing cartilage defect repair materials have shortcomings in mechanical properties and antibacterial properties, and are difficult to completely degrade, resulting in poor efficacy and may cause infection problems.

Method used

The preparation method of natural polysaccharide-based degradable high-strength antibacterial hydrogel is adopted. By mixing glacial acetic acid and high-viscosity chitosan into an aqueous solution with antibiotics and nano-hydroxyapatite, and adding gelatin and epoxy crosslinking agents. Antibacterial hydrogels are prepared through permeable cross-linking to ensure the mechanical properties and biocompatibility of the material.

Benefits of technology

The prepared antibacterial hydrogel has excellent mechanical properties, degradability and broad-spectrum antibacterial properties, which can effectively repair irregular defect areas and reduce the risk of infection. The preparation process is simple and cheap.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258271A_ABST
    Figure CN119258271A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of natural polysaccharide-based degradable high-strength antibacterial hydrogel. The preparation method comprises the following steps: 1) preparing glacial acetic acid and high-viscosity chitosan into an aqueous solution A; (2) preparing an aqueous solution B from antibiotics and nano-hydroxyapatite, wherein the mass ratio of the antibiotics to the nano-hydroxyapatite is (1: 2.5)-(1: 7.5); 3) mixing the aqueous solution A and the aqueous solution B, and adding gelatin into the mixed solution to obtain an aqueous solution C; 4) adding an epoxy cross-linking agent with a volume fraction of 0.5-1% into the aqueous solution C, centrifuging to remove bubbles, and eliminating micro-defects in the product to obtain a solution D; and 5) adding a normal saline solution containing 1wt%-5wt% of sodium hydroxide into the solution D, and carrying out permeation crosslinking to obtain the antibacterial gel. The antibacterial hydrogel can be formed in a mold with a complex shape, and irregular defects can be repaired.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cartilage defect repair, and in particular to a method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel. Background Art

[0002] Cartilage is a highly differentiated tissue without blood supply, nerve tissue and lymphatic vessels. Once injured, it cannot regenerate spontaneously in the body. Due to its special physiological structure, the reconstruction of cartilage or cartilage joints remains a considerable challenge. At present, a variety of treatment methods for osteoarthritis defect repair have been developed clinically, including autologous chondrocyte implantation, growth factor delivery, bone marrow stimulation (microfracture) and autologous transplantation. However, these methods usually have the problems of rapid efficacy attenuation (10 years old, 25-50%) and long recovery time (>12 months), especially for patients aged 40 to 50 years. At the same time, studies have shown that joint infection may occur around the prosthesis after total knee replacement. Bone joint infection is a serious orthopedic complication, and the current treatment methods are ineffective. Therefore, there is an urgent need to develop bone tissue engineering scaffold materials with good antibacterial properties, which can be closely integrated with the surrounding tissues of the defective body and promote tissue repair in situ.

[0003] Relevant patents on cartilage defect repair hydrogels have been reported in China, but there are still related problems that need to be solved. The Chinese invention patent publication with publication number CN202410358151.8 discloses a thermosensitive hydrogel and its application in cartilage defect repair. The thermosensitive hydrogel includes a chitosan-based solution, and the solute of the chitosan-based solution includes a chitosan-like solute. The chitosan-like solute includes at least one chitosan derivative, and the chitosan derivative has a functional group grafted on the molecular chain that makes the hydrogel thermosensitive. However, this method has disadvantages. Since chitosan derivatives are natural polymer derivatives, using them as a single gelling component will make it difficult for the mechanical properties of the gel to match the cartilage defect site, and it will often cause infection and inflammation at the defect site during the defect repair process. However, no relevant components with antibacterial functions are added to this thermosensitive hydrogel, which may cause an inflammatory response at the defect site or even cause serious infection, affecting the repair time and effect. The Chinese invention patent publication with publication number CN202410323063.4 discloses a method for preparing a type II collagen extracellular matrix cartilage graft. This method uses primary chondrocytes for in vitro culture, then removes cell-related components, removes glycosaminoglycans and other proteins, and retains a porous material based on type II collagen extracellular matrix for repair and treatment of cartilage defects. However, the preparation cycle of this material is long, and living animals are required to provide primary cells, the preparation cost is high, and the mechanical properties of this porous material are poor, which does not match the mechanical properties of cartilage tissue, making it difficult to repair the defect. The Chinese invention patent publication with publication number CN202311510291.4 discloses a porous composite scaffold for a cartilage defect model and a preparation method thereof. The porous composite scaffold for the cartilage defect model and the preparation method thereof treat the cartilage defect by combining Sr2+ / GO / βTCP / PEGDA with microfracture, but this porous composite scaffold itself is difficult to degrade and cannot completely repair the defect. In view of this, it is necessary to provide a method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel having excellent mechanical properties, antibacterial properties, and being completely degradable in the body and a product thereof. Summary of the invention

[0004] In view of this, the present invention provides a method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel.

[0005] The present invention specifically provides the following technical solutions:

[0006] A method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel, the preparation steps being:

[0007] 1) preparing aqueous solution A with glacial acetic acid and high viscosity chitosan;

[0008] 2) preparing the antibiotics and nano-hydroxyapatite into aqueous solution B, wherein the mass ratio of the antibiotics to the nano-hydroxyapatite is 1:2.5 to 1:7.5;

[0009] 3) mixing aqueous solution A and aqueous solution B, and adding gelatin to the mixed solution to obtain aqueous solution C;

[0010] 4) adding an epoxy crosslinking agent to aqueous solution C, removing bubbles by centrifugation, eliminating micro defects in the product, and obtaining solution D, wherein the volume fraction of the crosslinking agent is 0.5% to 1%;

[0011] 5) Adding a physiological saline solution containing 1 wt% to 5 wt% of sodium hydroxide into solution D for penetration cross-linking to obtain an antibacterial gel.

[0012] Furthermore, the mass ratio of the antibiotic to the nano-hydroxyapatite in step 2) is 1:2.5 to 1:5.

[0013] Furthermore, the mass ratio of the antibiotic to the nano-hydroxyapatite in step 2) is 1:5.

[0014] Furthermore, the viscosity of the high-viscosity chitosan in step 1) is greater than 400 mPa·s, the mass ratio of glacial acetic acid to high-viscosity chitosan is 1:1-1:3, the volume fraction of glacial acetic acid is 2%-6%, and the mass concentration of high-viscosity chitosan is 2%-10%.

[0015] Furthermore, in step 2), the concentration of the antibiotic in the aqueous solution B is 1-6 mg / mL, and the concentration of the nano-hydroxyapatite is 3-20 mg / mL.

[0016] Furthermore, in step 3), the mass ratio of gelatin to solution C is 1:5 to 1:15.

[0017] Furthermore, in the solution C described in step 3), the volume fraction of solution A is 40% to 80%, the mass concentration of gelatin is 2% to 10%, and the mixing temperature is 30 to 60°C.

[0018] Furthermore, the epoxy cross-linking agent in step 4) is epichlorohydrin.

[0019] Furthermore, the centrifugal speed in step 4) is 2000-4000 rpm / min, and the centrifugal time is 2-6 min.

[0020] Furthermore, the volume ratio of the physiological saline solution of sodium hydroxide in step 5) to the volume ratio of solution D is 1:0.5 to 1:2, and the cross-linking reaction temperature is 2 to 6°C.

[0021] The beneficial effect of the present invention is that: the present invention uses an alkaline solution to permeate chitosan to produce microcrystallization while epichlorohydrin is cross-linked to prepare an antibacterial hydrogel material. In the preparation, the ratio of nano-hydroxyapatite and cross-linking agent epichlorohydrin is strictly regulated, and the mechanical properties and physicochemical properties of the material are characterized, and it is found that these two components have a significant effect on the mechanical properties and physicochemical properties of the material. Too much addition of nano-hydroxyapatite and cross-linking agent epichlorohydrin will significantly affect the performance of the material, because too much nano-hydroxyapatite may affect the regular arrangement of other components, and it is a nano material itself, with a nano-enhancement effect, but too much addition will make the material brittle, and will also reduce the water content of the material system itself, which cannot meet the needs of the cartilage defect site; secondly, too little epichlorohydrin cannot make the system completely cross-linked, and the material modulus is low, and too much will be over-cross-linked, making it difficult for the polymer chain to slide, and also causing the material to become brittle. Therefore, after screening, the ratio of nano-hydroxyapatite and cross-linking agent epichlorohydrin that meets the requirements is determined. Moreover, the matrix material mainly uses chitosan and natural polymer gelatin, which can be completely degraded and endow the material with excellent biocompatibility. The antibacterial hydrogel can be formed in a mold with complex morphology and can repair irregular defects. In addition, the addition of gentamicin also gives the material a broad spectrum of antibacterial properties. At the same time, the raw materials for the preparation of the material are easy to obtain, the preparation process is simple, and the preparation cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings:

[0023] Figure 1 This is the compression strength test result diagram;

[0024] Figure 2 This is the result of 50% strain cyclic compression test;

[0025] Figure 3 This is the compression recovery rate test result diagram;

[0026] Figure 4 This is the tensile strength test result diagram.

[0027] Figure 5 This is the mass retention rate diagram of the antibacterial hydrogel after 28 days;

[0028] Figure 6 This is the result of the antibacterial performance test;

[0029] Figure 7 This is a diagram of the cytotoxicity test results. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0033] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 50 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0034] 3) Component 1 and component 2 were fully mixed at 55° C., 3 g of gelatin was added to the mixed solution, and dissolved and mixed uniformly at 55° C.;

[0035] 4) adding 225 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0036] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform penetration cross-linking to obtain the antibacterial hydrogel A1.

[0037] Example 2

[0038] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0039] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 100 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0040] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0041] 4) adding 225 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0042] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel A2.

[0043] Example 3

[0044] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0045] 2) Add 20 mg of gentamicin in 10 mL of saline solution and disperse 150 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0046] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0047] 4) adding 225 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0048] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel A3.

[0049] Comparative Example 1

[0050] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0051] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 50 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0052] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0053] 4) adding 450 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0054] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B1.

[0055] Comparative Example 2

[0056] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0057] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 100 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0058] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0059] 4) adding 450 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0060] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B2.

[0061] Comparative Example 3

[0062] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0063] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 150 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0064] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0065] 4) adding 450 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0066] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B3.

[0067] Comparative Example 4

[0068] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0069] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 50 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0070] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0071] 4) adding 900 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0072] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B4.

[0073] Comparative Example 5

[0074] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0075] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 100 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0076] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0077] 4) adding 900 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0078] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B5.

[0079] Comparative Example 6

[0080] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0081] 2) Add 20 mg of gentamicin in 10 mL of saline solution, and disperse 150 mg of nano-hydroxyapatite in the solution, i.e., component 2;

[0082] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0083] 4) adding 900 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0084] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B6.

[0085] Comparative Example 7

[0086] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 20 mL of normal saline solution;

[0087] 2) Add 20 mg of gentamicin in saline solution to 10 mL of saline solution, i.e., component 2;

[0088] 3) Component 1 and component 2 are fully mixed at 55°C. 3 g of gelatin is added to the mixed solution, dissolved at 55°C and mixed evenly;

[0089] 4) adding 225 μL of epichlorohydrin to the solution obtained in step 3) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0090] 5) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B7.

[0091] Comparative Example 8

[0092] 1) Add 1 mL of glacial acetic acid and 2.5 g of high viscosity (>400 mPa·s) chitosan, i.e., component 1, to 30 mL of normal saline solution;

[0093] 2) Component 1 was mixed thoroughly at 55°C. 3 g of gelatin was added to the mixed solution, dissolved and mixed uniformly at 55°C;

[0094] 3) adding 225 μL of epichlorohydrin to the solution obtained in step 2) and centrifuging the solution at 3500 rpm / min for 5 min to remove bubbles and eliminate micro defects in the product;

[0095] 4) At 4° C., 1.5 mL of 2 v / v% sodium hydroxide saline solution was added to the solution obtained in step 4) to perform osmotic cross-linking to obtain the antibacterial hydrogel B8.

[0096] Test Example 1 Compression Strength Test

[0097] The compressive strength of A1 to A3 of the embodiment and B1 to B6 of the comparative example were tested. The test process is as follows: The antibacterial hydrogels of the embodiment A1 to A3 and the comparative example B1 to B6 were subjected to a compression failure test using a universal testing machine. The compression test was performed at a speed of 2 mm / min until the material was destroyed. The stress-strain curve of the sample was plotted. The prepared antibacterial hydrogels A1-A3 and B1-B6 were screened according to the material's failure strength. Figure 1 This is the compression strength test result diagram.

[0098] from Figure 1 It can be seen that:

[0099] The compressive strength of B1~B6 is much lower than that of A1~A3. This is because the amount of cross-linking agent added in B1~B6 is higher than that in A1~A3, which leads to more cross-linking points in B1~B6. When forced to move, the polymer chain is restricted in movement due to too many cross-linking points, causing structural damage.

[0100] From B1 to B6, when the cross-linking agent content is high, as the content of nano-hydroxyapatite added in step 2) increases, the compressive strength of the material continues to decrease. This is mainly because when the degree of cross-linking of the material is relatively high, the number of cross-linking points increases, the movement of the polymer chain in the material is restricted due to cross-linking, and the ability of the material to consume energy through physical sliding of the molecular chain under the action of external force is reduced.

[0101] From A1 to A3, when the cross-linking agent content is low, as the content of nanohydroxyapatite added in step 2) increases, the compressive strength of the gel will also be significantly enhanced. This may be because nanohydroxyapatite is well dispersed in the gel, and because it has a large number of hydroxyl groups on its surface, it has good compatibility with chitosan and gelatin, which plays a nano-enhancement effect of inorganic nanoparticles on the matrix, effectively improving the strength of the gel. When the antibacterial hydrogel produces microcracks due to large deformation, the presence of nanoparticles has a certain effect of stopping silver streaks.

[0102] Test Example 2 50% strain cyclic compression test

[0103] The antibacterial hydrogels of Examples A1-A3 and Comparative Examples B1-B6 were subjected to compression recovery cycle tests using a universal testing machine. The test process is as follows: the compression test is performed at a speed of 2 mm / min, the target strain value is set to 50%, and 10 cycles are performed to characterize the compression recovery cycle of the material. The results of the 50% strain cycle compression test are shown in Figure 2. Figure 2 shown.

[0104] from Figure 2 It can be seen that:

[0105] The three materials B4, B5 and B6 had cracks in the first compression test and their structures were destroyed. This was mainly due to the excessive amount of epichlorohydrin added in step 4), which resulted in excessive crosslinking, dense crosslinking points, and limited polymer chain movement. Therefore, multiple cracks occurred during the large deformation process, which eventually led to material destruction. Therefore, the possibility of using these three materials for cartilage repair was ruled out.

[0106] Materials B1, B2 and B3 were damaged during the 5 cycles of compression. This was due to the excessive amount of epichlorohydrin added in step 4), which led to structural damage. Therefore, these three materials were excluded from the possibility of cartilage repair.

[0107] Among the three materials A1, A2 and A3, only A3 with the highest content of nanohydroxyapatite added in step 2) was damaged within 10 times, and neither A1 nor A2 was damaged in the 10-cycle compression test. This shows that A1 to A3 have good toughness, but A1 and A2 perform better, meet the support conditions in cartilage tissue, and are conducive to their application in cartilage defect repair and treatment.

[0108] In summary, since the amount of epichlorohydrin added in step 4) is lower in A1-A3 compared with B1-B6, the cross-linking density is also reduced. In the process of coping with large deformation, the molecular chain slippage in the polymer chain gradually plays a role and dissipates the energy applied by the outside world. The macroscopic manifestation of this process is that the material can withstand an increased number of cyclic compressions and is not easily damaged. Therefore, A1, A2 and A3 of the present invention have good toughness and are not prone to structural damage when the strain reaches 50%. It is suitable for use in the treatment of cartilage defects.

[0109] Test Example 3: Reply Performance Test

[0110] A1 and A2 that were not damaged after the cyclic compression test were subjected to a material recovery performance test after 10 cycles of cyclic compression. The test process is as follows: the compression test is performed at a speed of 2mm / min, the target strain value is set to 50%, and 10 cycles are performed to characterize the cyclic process of compression recovery of the material. The test results are shown in Figure 3 shown.

[0111] from Figure 3 It can be seen that:

[0112] The recovery performance of A2 is about 92%, which is significantly better than 87% of A1. The results of test 2 show that the recovery performance of A3 after compression cycle is slightly better than that of A2, but because the amount of nanohydroxyapatite added in step 2) is too high, it has local damage during the 50% strain cycle test, indicating that the amount of nanohydroxyapatite added in step 2) is more appropriate when 10 mg / mL, which can effectively enhance the matrix. Therefore, A2 with the best performance was selected for subsequent experiments.

[0113] Test Example 4 Tensile Properties Test

[0114] A2 with the best compression performance was selected for tensile performance test. B7 was used as a control. The test process is as follows: A2 and B7 were made into small specimens with a cross-sectional width of 3mm and a thickness of 0.5mm through a mold and the tensile strength was tested at a speed of 1mm / min.

[0115] The tensile properties test results are as follows Figure 4 As shown. Figure 4 It can be seen that:

[0116] The tensile strength of A2 nano-enhanced by adding nano-hydroxyapatite in step 2) is about 4.5 times that of B7 without adding nano-hydroxyapatite. This indicates that adding nano-hydroxyapatite in step 2) to achieve nano-enhancement effect can effectively improve the mechanical properties of the material.

[0117] Test Example 5 Degradation Performance Test

[0118] In the process of cartilage regeneration, the material should have a certain degradation rate. While supporting cell growth, it also needs to provide growth space for new tissues through degradation. Therefore, a 28-day degradation test was conducted on B7, A1, A2, and A3. The test process is as follows: B7, A1, A2, and A3 were placed in a 48-well plate containing 2 mL of PBS buffer in each well, and placed in a constant temperature incubator at 37°C. Samples were taken at predetermined time intervals (1, 4, 7, 14, and 28 days). The degradation was evaluated by evaluating the dry weight loss between two immersions, and the degradation rate of the material was calculated by the degradation rate equation.

[0119] Figure 5 This is the result of the 28-day degradation test. Figure 5 It can be seen that:

[0120] After 28 days of degradation, the degradation rates of the four materials B7, A1, A2, and A3 did not exceed 20%.

[0121] It is shown that the relatively slow degradation rate of the antibacterial hydrogel of the present invention allows it to be retained in the implanted area for a long time to support cell growth. For the repair of full-thickness cartilage defects, the repair time required for tissue defects at the trauma site is longer, and the degradation rate of this material can match the repair rate of the cartilage defect site, and is suitable for filling and repairing the defect site.

[0122] Test Example 6 Sterilization Performance Test

[0123] B7, A1, A2 and A3 antibacterial hydrogels were selected for antibacterial tests on Staphylococcus aureus and Escherichia coli. At the same time, B8 hydrogel without antibiotics was used as a control. The test process is as follows: Escherichia coli and Staphylococcus aureus (4 μL) were added to 4 mL of culture medium and cultured at 37 °C for 12 h. The bacterial suspension was then diluted to 2 × 10 5 CFU / mL for later use. Add B7, A1, A2 and A3 with a diameter of 4 mm and a thickness of 3 mm to a 96-well plate, and add 200 μL of diluted bacterial solution to each well after ultraviolet disinfection. Continue to culture the sample and bacterial solution in a 37°C incubator for 24 hours, and use an enzyme marker to measure the absorbance of the liquid in different wells at a wavelength of 600 nm. Figure 6 This is a graph showing the bactericidal performance test results.

[0124] from Figure 6 It can be seen that:

[0125] The four groups of materials with added antibiotics, B7, A1, A2 and A3, have a sterilization rate of more than 95% against Staphylococcus aureus and Escherichia coli, and the nanohydroxyapatite added in step 2) does not affect the antibacterial properties of the materials, proving that they can inhibit the occurrence of bacterial inflammation after being implanted in the defect site.

[0126] Test Example 7 Cytotoxicity Test

[0127] A2 was selected as a representative sample to evaluate the in vitro biocompatibility of the antibacterial hydrogel material of the present invention. The cytotoxicity of A2 to bone marrow mesenchymal stem cells (BMSC) and mouse embryonic osteoblasts (MC3T3-E1) was detected by the extract method, and B7 obtained in Comparative Example 7 was used as the control group. The test process is as follows: 10% fetal bovine serum, 100U / mL penicillin and 100μg / mL streptomycin were added to the cell culture medium. The cells were cultured in a carbon dioxide humidified incubator at a culture temperature of 37°C, and the cell culture medium was replaced every two days. 200μL of culture solution was added to each container containing B7 and A2 antibacterial hydrogel sheets with a diameter of 4mm and a thickness of 3mm for extraction. The extraction temperature was 37°C and the extraction time was 24h. 20,000 bone marrow mesenchymal stem cells (BMSC) and mouse embryonic osteoblasts (MC3T3-E1) were seeded in each well of a 48-well plate. After culturing for 12 hours, the normal culture medium was replaced with the extract and cultured for another 24 hours. Finally, the cell activity was determined using the thiazolyl blue colorimetric method.

[0128] Figure 7 Figure 2 is the result of cytotoxicity test. Figure 7 It can be seen that:

[0129] The activity of A2 relative to bone marrow mesenchymal stem cells (BMSC) and mouse embryonic osteoblasts (MC3T3-E1) was 99% and 97%, respectively, indicating that the material itself has good biocompatibility and the release of antibiotics has no toxicity to cells.

[0130] In summary, the present invention forms a crystal region and covalently cross-links chitosan and gelatin from natural sources, and then dopes the antibiotic gentamicin and nano-hydroxyapatite. After mechanical property tests, degradation tests and antibacterial tests, the present invention obtains a natural polysaccharide-based degradable high-strength antibacterial hydrogel with excellent mechanical properties, degradability and antibacterial properties. This antibacterial hydrogel meets the mechanical property requirements of the cartilage part and provides a new idea for the research and development of materials required for the treatment of infected cartilage defects.

[0131] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel, characterized in that: The preparation steps are: 1) preparing aqueous solution A with glacial acetic acid and high viscosity chitosan; 2) preparing the antibiotics and nano-hydroxyapatite into aqueous solution B, wherein the mass ratio of the antibiotics to the nano-hydroxyapatite is 1:2.5 to 1:7.5; 3) mixing aqueous solution A and aqueous solution B, and adding gelatin to the mixed solution to obtain aqueous solution C; 4) adding an epoxy crosslinking agent to aqueous solution C, removing bubbles by centrifugation, eliminating micro defects in the product, and obtaining solution D, wherein the volume fraction of the crosslinking agent is 0.5% to 1%; 5) Adding a physiological saline solution containing 1 wt% to 5 wt% of sodium hydroxide into solution D for penetration cross-linking to obtain an antibacterial gel.

2. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The mass ratio of the antibiotic to the nano-hydroxyapatite in step 2) is 1:2.5 to 1:

5.

3. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The mass ratio of the antibiotic to the nano-hydroxyapatite in step 2) is 1:

5.

4. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The viscosity of the high-viscosity chitosan in step 1) is greater than 400 mPa·s, the mass ratio of glacial acetic acid to high-viscosity chitosan is 1:1-1:3, the volume fraction of glacial acetic acid is 2%-6%, and the mass concentration of high-viscosity chitosan is 2%-10%.

5. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: Step 2) The concentration of the antibiotic in the aqueous solution B is 1-6 mg / mL, and the concentration of the nano-hydroxyapatite is 3-20 mg / mL.

6. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: Step 3) The mass ratio of gelatin to solution C is 1:5 to 1:

15.

7. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: In the solution C described in step 3), the volume fraction of solution A is 40% to 80%, the mass concentration of gelatin is 2% to 10%, and the mixing temperature is 30 to 60°C.

8. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The epoxy cross-linking agent in step 4) is epichlorohydrin.

9. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The centrifugal speed in step 4) is 2000-4000 rpm / min, and the centrifugal time is 2-6 min.

10. The method for preparing a natural polysaccharide-based degradable high-strength antibacterial hydrogel according to claim 1, characterized in that: The volume ratio of the sodium hydroxide physiological saline solution in step 5) to the volume ratio of solution D is 1:0.5 to 1:2, and the cross-linking reaction temperature is 2 to 6°C.

Citation Information

Patent Citations

  • Porous composite scaffold of cartilage defect model and preparation method of porous composite scaffold

    CN117679558A

  • Temperature-sensitive hydrogel and application thereof in cartilage defect repair

    CN118206778A

  • Preparation method of II-type collagen extracellular matrix cartilage graft

    CN118236551A